IKKα is involved in kidney recovery and regeneration of acute ischemia/reperfusion injury in mice through IL10-producing regulatory T cells - Xin Wan; Li-Jun Hou; Li-Yuan Zhang; Wen-Juan Huang; Lin Liu; Qian Zhang; Bo Hu; Wen Chen; Xin Chen; Chang-Chun Cao (The Company of Biologists, 2015)
The recovery phase after kidney ischemia/reperfusion (IR) injury is often associated with the suppression of inflammation and the proliferation of tubular epithelial cells (TECs). The duration of this phase is often determined by the suppression of inflammation and the proliferation of TECs. Several lines of evidence suggest that IκB kinase α (IKKα) not only promotes the production of anti-inflammatory factors and/or prevents the production of inflammatory factors, but also induces the accompanying cell differentiation and regeneration, and suppresses inflammation. We therefore hypothesized that IKKα could participate in the kidney repair after IR injury and have used a mouse model of acute kidney injury (AKI) to test this. We found that IKKα mediated the repair of the kidney via infiltrated regulatory T (Treg) cells, which can produce anti-inflammatory cytokine IL10, and that IKKα also increased the proliferation of the surviving TECs and suppressed of inflammation. In addition, the expression of indoleamine 2,3-dioxygenase (IDO) in TECs is consistent with the infiltration of IL10-producing Treg cells. We conclude that IKKα is involved in kidney recovery and regeneration through the Treg cells that can produce IL10, which might be a potential therapeutic target that can be used to promote kidney repair after IR injury.